Environmental Disclosure Under CEO Influence: The Silent Role of Female Board Members - Asiah, Nur; Rahmawati, Wulan (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Indonesia, as one of the major greenhouse gas emitters in Southeast Asia, faces growing pressure to strengthen environmental transparency through carbon emission disclosures in corporate reporting. This study aims to examine the effect of institutional ownership and chief executive officer (CEO) power on carbon emission disclosure (CED) in energy sector companies listed on the Indonesia Stock Exchange during 2020–2023, with female directors as a moderating variable. Using a sample of 13 companies (52 firm-year observations), data were obtained from annual and sustainability reports. The analysis employed a random effect regression model, supported by diagnostic tests for normality, multicollinearity, and heteroskedasticity. The CED index was used to measure disclosure levels, while CEO power was measured using a composite index consisting of duality, tenure, education, share ownership, and age. The results indicate that institutional ownership has a negative effect on carbon emission disclosure, while CEO power has a positive and significant effect. Furthermore, the presence of female directors does not moderate the relationship between institutional ownership and carbon emission disclosure, nor does it moderate the relationship between CEO power and carbon emission disclosure. These findings emphasize the crucial role of CEO leadership in enhancing environmental transparency and suggest that female directors’ influence in sustainability governance remains limited within Indonesia’s energy sector.